Halal Trust Score sebagai Inovasi Penilaian Pembiayaan Syariah: Sebuah Prototipe pada Halal Value Chain berbasis Blockchain - Pradananta, Galih; Dana, Badara Shofi (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
The global halal industry is undergoing a paradigm shift from voluntary compliance to mandatory state-enforced assurance, particularly in Indonesia, where the halal food sector is a critical pillar of the national economy. However, the current halal certification regime remains predominantly product-centric and relies on static, document-based verification. This creates a significant information asymmetry for Islamic Financial Institutions (IFIs) when assessing the creditworthiness and Sharia compliance of Micro, Small, and Medium Enterprises (MSMEs). This research proposes the